Analisis Sistem Website I-Simpel Indosat Ooredoo Hutchison Sales Area Jambi berdasarkan Teori Golden Rules of User Interface Design Theo Mandel - Miftahul Jannah; Eka Rahmawati; Deva Ardhana Sapura; Albet Triadi (Journal on Education, 2023)
One of the failures of a system is due to a user interface error that is too complicated. A complicated user interface actually makes users confused about using the system. This study aims to analyze the interface design on the I-simple website system. User interface analysis The I-simple website system uses Theo Mandel's golden rule of user interface design approach. In the golden rules of user interface design" are divided into three things, namely placing the user as control, making it easier for the user to remember, and interface consistency. So that this analysis can be used as material for consideration and reference in the design and performance of the I-simple system. Based on the results of the analysis, it is stated that in general the interface design and usability of the I-simple website system are good, but there are still a number of things that need to be improved, especially in language and submenus.